Bioversity International in Focus - Cherfas, J. (2007)
Biological diversity encompasses all the variation in living things on Earth. Part is used by people to meet their needs for food, shelter, medicines, building materials and so on. That portion is usually referred to as agricultural biodiversity. Bioversity International exists to conduct research on agricultural biodiversity that will enable poor people to improve their livelihoods. This booklet outlines the areas of agricultural biodiversity on which the organization focuses.